The effect of sensory marketing in enhancing the mental image of the customer)Applied research( - abidalghafoor, Qutaiba amjed (Journal of Economics and Administrative Sciences, 2021)
The research aims to study the extent of the influence of the dimensions of sensory marketing on the perceptual mental image of customers, knowing the type of relationships that link the dimensions of sensory marketing with each other, no one from the researcher mentioned (as far as the researcher knows) the link between sensory marketing and mental image, from this point of view the main goal is determined, the effect of sensory marketing on the mental image taken from customers, as the research was conducted on a number of first-class restaurants represented (Chef City, Chili House, Mado, Fried Chicken Saj Alreef) and the research community was represented by the customers of the aforementioned restaurants, and a random sample was chosen that included (206) customers from the five restaurants customers. The questionnaire was the main tool in collecting data and information, as it was sent electronically and randomly to customers. Among the most prominent statistical methods are the standard deviation, the arithmetic mean, the Pearson correlation coefficient, and the simple linear regression coefficient, and the most prominent results reached by the research were the existence of an influence relationship of Sensory Marketing on the mental image built by customers around the restaurants in question, but it differs according to the restaurant, as well as the existence of a relationship A link between sensory marketing and the perceived mental image of the customer. The current research is considered a general review of the concept of sensory marketing and its effect in enhancing the perceived mental image of the customer